2018
DOI: 10.22452/jdbe.vol18no1.3
|View full text |Cite
|
Sign up to set email alerts
|

The environmental factors affecting service satisfaction of community hospital

Abstract: Community Hospital in Thailand is a small-size hospital and available at a 'local level. Established by the Thai government some thirty years ago, the hospitals now find their facilities are unable to cope with increasing numbers of patients due to population growth. The re-furbishment of the old buildings in the hospital was needed in order to respond to these changes. Past extensions to the hospitals have focused more on form and function of the built environment rather than "needs" of the users (patients/fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Interior design features include: art works, plants (nature), television, color scheme, furniture, and signage. This model was also used by Pongyen & Waroonkun (2015) and Waroonkun (2018), with the addition of a further category: 'outdoor environment features'. Outdoor environment features relate to those services and activities that are not part of the actual waiting area but are considered to be part of the OPD users experience and to have an impact on users' level of anxiety/comfort.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Interior design features include: art works, plants (nature), television, color scheme, furniture, and signage. This model was also used by Pongyen & Waroonkun (2015) and Waroonkun (2018), with the addition of a further category: 'outdoor environment features'. Outdoor environment features relate to those services and activities that are not part of the actual waiting area but are considered to be part of the OPD users experience and to have an impact on users' level of anxiety/comfort.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Figure 2. The hierarchy structure of environmental factors in a hospital building (Harris et al, 2002;Waroonkun, 2018) Considering the role of 'stress' in a 'supportive environment', it is important that the hospital environment should not exacerbate any stress experienced by an outpatient user but rather be designed to reduce such stress. Community hospital users' satisfaction with features of the physical environment will be influenced by the extent to which those features can mitigate their feelings of stress.…”
Section: Literature Reviewmentioning
confidence: 99%
“…During the COVID outbreak, the whole community hospital infrastructure was overwhelmed with a high number of patients, causing hygiene and safety standards to become a priority in every hospital. However, the current hygiene standards are outdated and the hospitals were not prepared for the spread of unprecedented respiratory infectious diseases, leading to low-efficiency services in the hospitals (Waroonkun, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…3130 (Figure 1); most of the buildings were built in the 1990s. A recent study conducted by Waroonkun (2018) revealed that most community hospital OPD buildings are obsolete and require rebuilding or renovation. The study also demonstrated that most of the buildings have been through multiple renovations without considering the hygiene standards that would have helped in preventing the spread of COVID-19 (Thailand Ministry of Public Health, 2017;Thailand Ministry of Public Health, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This study addresses how the limited visual capacity of the patient needs to be considered in providing the patients with the view of the natural outdoor environment. Research has suggested that the outdoor view has an impact on the patient's healing and recovery process (Waroonkun, 2018). Patients assigned to the room with a windows view tend to experience faster recovery, show fewer complaints, and require fewer doses of the medicine than the patients in the room without a windows view (Ulrich, 1984).…”
Section: Introductionmentioning
confidence: 99%